Psychopathology in patients with schizophrenia attending a psychiatry outpatient clinic at a tertiary care hospital - Wijesundara, Hiranya; Dayabandara, Madhubhashinee; Ellepola, Arjuna; Hanwella, Raveen (Sri Lanka Journal of Psychiatry, 2011)
Background: Patients with schizophrenia who are not acutely ill continue to experience different levels of psychopathology, despite a relatively stable lifestyle. Aims: To describe the pattern of symptoms in patients with schizophrenia attending an outpatient clinic using the Brief Psychiatric Rating Scale Expanded version (BPRS-E). Methods: Consecutive patients in an outpatient clinic, with a diagnosis of schizophrenia were assessed. Analysis was based on the four-factor cluster of symptoms: thought disturbance, animation, mood disturbance and apathy identified using the BPRS-E. Results: Sample size was 178 (males 54.5 %, mean age = 39.29 years, mean illness duration = 13.29 years, mean total BPRS score = 32.11). Apathy had the highest mean score among the symptom clusters (6.54, SD 3.56), while blunted affect (1.87, SD 1.23) and emotional withdrawal (1.85, SD 1.26) had highest individual item mean scores. Patients on clozapine had significantly more symptoms of thought disturbance and animation compared to others, (P <0.05). There was no significant difference in symptoms between patients on typical and atypical antipsychotics. Those on higher doses of clozapine (>400mg) had significantly higher scores in thought disturbance and apathy. Higher scores on total BPRS, negative symptoms and thought disturbance were associated with lower levels of functioning. Conclusions: Patients with schizophrenia on treatment continue to have symptoms. Negative symptoms are the most predominant. Patients on clozapine have a higher level of psychopathology. The degree of negative symptoms and thought disturbance had a significant association with the level of functioning.
Keywords: Psychopathology; schizophrenia